Jesus' Teaching on Divorce: Lessons for Fruitful Feminist Engagement with Society - Muonwe, Michael (The international journal of religion and spirituality in society, 2016)
This article takes a critical stance against the opinion of radical, post-Christian feminist theologians who argue that Christianity is inherently misogynist and patriarchal and, thus, cannot guarantee the liberation of women from oppression. I will demonstrate that Christianity’s core message is that of liberation from every form of oppression and bondage, including gender-based ones. Without denying that Christianity has historically encouraged women’s oppression, I will use the critical stance of Jesus against the exploitative and patriarchal structures of his day to buttress the significance of the Christian message in confronting gender inequality in all its ramifications. Of special importance in the article is the discussion of Jesus’ attitude toward the traditional Jewish institution of marriage, which can serve as a source of inspiration for women as they fight androcentric oppressive structures in the present society.